2019
DOI: 10.1186/s12985-019-1177-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the yield of oropharyngeal swabs and sputum for detection of 11 common pathogens in hospitalized children with lower respiratory tract infection

Abstract: Background Advances in molecular laboratory techniques are changing the prospects for the diagnosis of viral infectious diseases. Multiplex polymerase chain reaction assay (multiplex-PCR) can detect dozens of pathogens simultaneously, greatly reducing turnaround time (TAT) and improving detection sensitivity. But as a double-edged sword, due to the high sensitivity of PCR, the type of respiratory specimens is critical to diagnosis. In this work, we performed a head-to-head comparison to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Currently, nucleic acid amplification techniques (NAATs) (such as PCR and multiplex PCR) have been increasingly used for identification of pathogens in infectious respiratory diseases; and one of the multiplex‐PCR technology, GenomeLab gene expression profiler genetic analysis system (GeXP)‐based assay (developed by Beckman Coulter), has been adopted in the infectious pathogens diagnostics; this detection technique has been applied in clinical for over 5 years; however, more clinical application studies are still necessary, especially in southeast China. GenomeLab gene expression profiler genetic analysis system is a high‐sensitive and specific analytical platform for high‐throughput nucleic acid detection based on capillary electrophoresis separation technology, multiple gene analysis technology, and high‐sensitivity laser‐induced fluorescence technology .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, nucleic acid amplification techniques (NAATs) (such as PCR and multiplex PCR) have been increasingly used for identification of pathogens in infectious respiratory diseases; and one of the multiplex‐PCR technology, GenomeLab gene expression profiler genetic analysis system (GeXP)‐based assay (developed by Beckman Coulter), has been adopted in the infectious pathogens diagnostics; this detection technique has been applied in clinical for over 5 years; however, more clinical application studies are still necessary, especially in southeast China. GenomeLab gene expression profiler genetic analysis system is a high‐sensitive and specific analytical platform for high‐throughput nucleic acid detection based on capillary electrophoresis separation technology, multiple gene analysis technology, and high‐sensitivity laser‐induced fluorescence technology .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suspected the reasons for their findings was due to varied M. pneumoniae density in the NP swab specimens, which were collected in a blinded fashion, and the larger OP swab tip, which was able to reach deeper into the airway resulting in a specimen higher load of M. pneumoniae. In addition, it has been reported that a higher copy number of M. pneumoniae is found in the alveoli than on the epithelium of the upper respiratory tract [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of recently published studies focus on the development of molecular methods to solve multiple detection in one reaction [5,13,14,18,19]. The multiplex-PCR methods has been previously evaluated versus conventional techniques [1,6,8,20] or single-plex PCR [21].…”
Section: Discussionmentioning
confidence: 99%
“…DNA/RNA extraction is performed on an automated workstation (Smart LabAssist-16/32, Health Gene Technologies, China) [14]. A total of 200µL of lique ed sputum was used for nucleic acid extraction and eluted in 30µL, which was divided into two parts for ResP-CE and XYres-MCA analysis, respectively.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
See 1 more Smart Citation